Antibacterial properties of Ginkgo biloba extract on microorganism strains in vitro experiments - Fotina, Tetiana; Фотіна, Тетяна; Petrov, Roman; Петров, Роман; Fotina, Hanna; Фотіна, Ганна; Shkromada, Oksana; Шкромада, Оксана; Yaroshchuk, Roman; Ярощук, Роман; Fotin, Anatoliy; Фотін, Анатолій; et al. (University of Agronomic Sciences and Veterinary Medicine of Bucharest, 2024)
The pressing issue of antibiotic resistance demands immediate attention. Scientists are exploring alternative remedies, including plant-based solutions, to prevent infectious diseases. This study investigates the antibacterial properties of Ginkgo biloba extract in vitro. Ginkgo biloba contains specific compounds - terpenlactones (terpenic lactones: ginkgolides, bilobalides) and flavonoglycosides (flavonoids: quercetin, kaempferol, isorhamnetin, proanthocyanidins), which regulate metabolic processes, normalize cellular metabolism, and improve blood rheology and microcirculation. The research aims to examine the antimicrobial effects of ethanolic Ginkgo biloba extract on various strains of microorganisms in experiments conducted in vitro. The antibacterial activity of the plant extract was evaluated using the disc diffusion method against reference strains of Enterobacteriaceae, Pseudomonadaceae, Staphylococcaceae, Bacillaceae, Listeriaceae, Campylobacter jejuni, Corynebacterium xerosis, and Candida albicans. The experiments demonstrated significant antibacterial efficacy against a range of microorganisms, suggesting the potential of Ginkgo biloba extracts in combating polyresistant strains. This research received support from the Ministry of Education and Science of Ukraine (grant 0117U006533). Актуальна проблема стійкості до антибіотиків вимагає негайної уваги. Вчені досліджують альтернативні засоби, зокрема розчини на рослинній основі, для запобігання інфекційним захворюванням. Це дослідження досліджує антибактеріальні властивості екстракту гінкго білоба in vitro. Гінкго дволопатеве містить специфічні сполуки - терпенлактони (терпенові лактони: гінкголіди, білобаліди) і флавоноглікозиди (флавоноїди: кверцетин, кемпферол, ізорамнетин, проантоціанідини), які регулюють обмінні процеси, нормалізують клітинний метаболізм, покращують реологію крові та мікроциркуляцію. Дослідження спрямоване на вивчення антимікробної дії спиртового екстракту гінкго білоба на різні штами мікроорганізмів в експериментах, проведених in vitro. Антибактеріальну активність рослинного екстракту оцінювали методом дискової дифузії проти еталонних штамів Enterobacteriaceae, Pseudomonadaceae, Staphylococcaceae, Bacillaceae, Listeraceae, Campylobacter jejuni, Corynebacterium xerosis та Candida albicans. Експерименти продемонстрували значну антибактеріальну ефективність проти ряду мікроорганізмів, що свідчить про потенціал екстрактів гінкго білоба в боротьбі з полірезистентними штамами. Дослідження підтримано Міністерством освіти і науки України (грант 0117U006533).
Антибактеріальні властивості екстракту Гінкго білоба на штамах мікроорганізмів в експериментах in vitro
Зажарський Володимир Володимирович https://orcid.org/0000-0003-2674-2494
Keywords: reference strains; референтні штами; antibacterial properties; антибактеріальні властивості; disc diffusion method; метод дискової дифузії; Ginkgo biloba; гінкго білоба